Emotions in Argumentative Narration: The Case of the Charlie Hebdo Attack - Cigada, Sara (Informal Logic, 2019)
This paper studies emotional inferencing triggered by emotion terms using Pragma-Dialectics and the Argumentum Model of Topics. The corpus, in French, is an excerpt of a video-recorded testimony in which a middle school teacher evokes her experience of being in class the day after the Charlie Hebdo attack, thus presenting a case of argumentation in context. The analysis focuses on the argumentative structure and on the rhetorical strategies that trigger emotional inferencing. The emotional inferencing derives from a Locus of Ontological Implication, which links a situation and an emotion (and vice-versa), while the culture-bound elements tend to be part of the endoxon.